Perancangan Sistem Administrasi Pengelolaan Arsip Surat Masuk Dan Keluar Pada Biro Kesejahteraan Rakyat Berbasis Web - Salsabila Arifa Hasibuan; Zahara Vonna; Ahmad Taufik Al Afkari Siahaan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Managing incoming and outgoing letter archives is an important aspect in supporting administrative performance at the Regional Secretary's People's Welfare Bureau. This research aims to design a web-based administration system that can increase effectiveness and efficiency in managing mail archives. The methods used in this research include requirements analysis, system design, and prototype testing. The results of the analysis show that the mail management process is currently still carried out manually, which results in difficulties in searching and archiving data. By designing a web-based system, it is hoped that it will make it easier for users to input, search and manage mail archives in real-time. The resulting system prototype is equipped with features such as mail data management, reports and notifications, which are designed to increase data accessibility and security. Test results show that this system can function well and meet user needs. It is hoped that this research can make a positive contribution to the Regional Secretary's People's Welfare Bureau in improving administrative performance through better archive management.